Contact metamorphism of the Tethyan Sedimentary Sequence, Upper Mustang region, west-central Nepal. (24th November 2020) - Lihter, Iva; Larson, Kyle P.; Shrestha, Sudip; Cottle, John M.; Brubacher, Alex D.
Abstract: The Upper Mustang region of west-central Nepal contains exposures of metamorphosed Tethyan Sedimentary Sequence rocks that have been interpreted to reflect either contact metamorphism related to the nearby Mugu pluton or regional metamorphism associated with the North Himalayan domes. New monazite geochronology results show that the Mugu leucogranite crystallized at c. 21.3 Ma, while the dominant monazite age peaks from the surrounding garnet ± staurolite ± sillimanite schists range between c. 21.7 and 19.4 Ma, generally decreasing in age away from the pluton. Metamorphic temperature estimates based on Ti-in-biotite and garnet–biotite thermometry are highest in the specimens closest to the pluton (648 ± 24°C and 615 ± 25°C, respectively) and lowest in those furthest away (578 ± 24°C and 563 ± 25°C, respectively), while pressure estimates are all within uncertainty of one another, averaging 5.0 ± 0.5 kbar. These results are interpreted to be consistent with contact metamorphism of the rocks in proximity to the Mugu pluton, which was emplaced at c. 18 ± 2 km depth after local movement across the South Tibetan detachment system had ceased. While this new dataset helps to characterize the metamorphic rocks of the Tethyan Sedimentary Sequence and provides new constraints on the thickness of the upper crust, it also emphasizes the importance of careful integration of metamorphic conditions and inferred processes that may affect interpretation of currently proposed Himalayan models.